Kinerja Yang Dihasilkan Dari Efek Pluntiran Pada Turbin Hidrokinetik Savonius Tornado Tanpa End Plate - Sembiring, Vio Altara; Nindito, Dwi Anung; Jaya, Allan Restu (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2025)
Savonius Tornado Hydrokinetic Turbine has an optimal capture area, but is less able to transmit the thrust of water kinetic energy into electrical energy. The purpose of this study is to analyze the Savonius Tornado Hydrokinetic Turbine twisted without an end plate. The experimental method was carried out on the flume channel to compare the performance between the Conventional Savonius Hydrokinetic Turbine and the Savonius Tornado Turbine without an end plate by twisting the turbine blades 1/2D, 1/3D, 4/4D, where D is the width of the turbine end plate. This test will obtain the Coefficient of power (Cp), RPM, torque (τ) and TSR as parameters to see the turbine performance. This experimental study used a flow velocity (v) between 0.322 m/s - 0.507 m/s. The results of the study indicate that the Conventional Savonius Turbine produces a torque value of 0.040 Nm - 0.095 Nm, the 1/2D Savonius Tornado turbine without a twisted end plate produces a torque value of 0.051 Nm - 0.194 Nm, the 3/4D Savonius Tornado turbine without a twisted end plate produces a torque value of 0.049 Nm - 0.155 Nm, and the 4/4D Savonius Tornado turbine without a twisted end plate produces a torque value of 0.044 Nm - 0.168 Nm. The Savonius Tornado Hydrokinetic Turbine is twisted without end plates, resulting in increased turbine performance